Occurrence, Characterization, and Antimicrobial Susceptibility of Salmonella enterica in Slaughtered Pigs in Sardinia. Issue 4 (22nd February 2017) - Fois, Federica; Piras, Francesca; Torpdahl, Mia; Mazza, Roberta; Consolati, Simonetta G.; Spanu, Carlo; Scarano, Christian; De Santis, Enrico P. L.
Abstract: The aim of this study was to determine Salmonella occurrence in slaughtered finishing pigs and piglets and in slaughterhouse environment in order to characterize the isolates with phenotypical (antimicrobial testing) and molecular (PFGE, MLVA) methods. Nine slaughterhouses located in Sardinia were visited. Six hundred and eight samples collected from 106 pigs and 108 environmental samples were collected and analyzed. Salmonella was isolated in 65 of 504 (12.9%) samples from finishing pigs, with an occurrence of 15.1% in colon content, 12.7% in lymph nodes and liver, and 11.1% in carcass surface samples. Salmonella was never detected in piglets. The combined results of serotyping and PFGE showed a possible self‐contamination in 71.5% of Salmonella positive carcasses of lymph nodes and/or colon content carriers, pointing out the role of healthy pigs for carcass contamination. A significantly higher ( P < 0.05) occurrence was detected in finishing pigs of EC countries origin (23%) than in pigs of local farms (8%). Salmonella was also detected in 3.7% of environmental samples. The most prevalent serovar was S . Anatum, followed by S . Rissen, S . Derby, and monophasic S . Typhimurium. Resistance to at least 3 antimicrobial was observed in 97.1% of strains and 7 different patterns of multiple resistance were identified. The most common resistance was detected against sulphonamide compounds. A strict slaughterhouse application of hygiene standards is essential to control the risk of Salmonella contamination.